PERTANGGUNGJAWABAN PIDANA TERHADAP PENYALAHGUNAAN NARKOTIKA DALAM MASA REHABILITASI (Studi Putusan Pengadilan Negeri Lubukpakam No. 1995/PID.SUS/2017/PN.LBP) - Kharisma S Ginting; Alvi Syahrin; Madiasa Ablisar; Marlina Marlina (USU LAW JOURNAL, 2019)
ABSTRACT Decision of the LubukPakam District Court No. 1995/Pid.Sus/2017/PN.Lbp dropped in accordance with the demands of the public prosecutor, guilty of violating article 112 paragraph (1) of Law no. 35 of 2009 on Narcotics should be known to be in the rehabilitation period of the narcotics then the judge handed down the rehabilitation decision in accordance with Article 103 paragraph (1) of Law no. 35 of 2009 on Narcotics does not impose a prison sentence accompanied by a fine. Therefore, it is necessary to examine the rule of law concerning narcotics abuse and drug abuse victims against people in the rehabilitation period. Criminal liability for the misuse of narcotics during the rehabilitation and punishment against abuse of narcotics during rehabilitation at the decision of LubukPakam District Court. 1995/Pid.Sus/2017/PN.Lbp. Keywords: Addiction, Abuse and Rehabilitation